2014
DOI: 10.1520/mpc20140024
|View full text |Cite
|
Sign up to set email alerts
|

Production of Austempered Gray Iron (AGI) Using Forced Air Cooling

Abstract: This paper presents the outcome of the production of austempered gray iron (AGI) using forced air cooling as the quenching medium. Samples from Class 20 gray cast iron were prepared for micrographic analysis, x-ray diffraction (XRD) analysis, and mechanical testing. The prepared samples were austenitized at 920°C, soaked for 1 h, force air-cooled to the austempering temperature range of 250°C to 400°C (at 25°C intervals), held for another hour at the austempered temperature to allow for complete phase transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The increase in elemental magnesium concentrations can be attributed to the intrinsic spontaneous reactivity of ferro-magnesium alloys. This level of magnesium is known to promote vigorous melt reaction and reduction in recovery (Hatung et al, 2014;Olawale et al, 2014). For example, high magnesium content, greater than 10 wt.…”
Section: A Composition Of Calcined Cashew Nut Shell Ashmentioning
confidence: 99%
“…The increase in elemental magnesium concentrations can be attributed to the intrinsic spontaneous reactivity of ferro-magnesium alloys. This level of magnesium is known to promote vigorous melt reaction and reduction in recovery (Hatung et al, 2014;Olawale et al, 2014). For example, high magnesium content, greater than 10 wt.…”
Section: A Composition Of Calcined Cashew Nut Shell Ashmentioning
confidence: 99%
“…Hsu and Chen [10] concluded that the enhancement of corrosion resistance in ADI was due to the presence of retained austenite as a result of austempering. Similar studies with GCI are also common where the corrosion resistance and the mechanical properties were improved dramatically by tailoring the heat treatment pattern (tempering, austempering, and quenching [11,12,13,14]) and by alloy additions [8]. Further improvement of the mechanical properties, compared to those of conventional GCI, was observed in austempered gray cast iron (AGCI) due to the formation of a matrix of ausferritic structures (ferrite and stabilized austenite) or bainitic ferrite during austempering [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…Further improvement of the mechanical properties, compared to those of conventional GCI, was observed in austempered gray cast iron (AGCI) due to the formation of a matrix of ausferritic structures (ferrite and stabilized austenite) or bainitic ferrite during austempering [12,15]. Thus, the domain of applicability of AGCI is even wider than that of GCI due to its favorable combination of enhanced mechanical properties [11,12,13,14,15] and improved wear characteristics [15,16,17]. The present literature, however, is lacking in reporting the corrosion behavior of AGCI, although a lot of work can be found on testing the corrosion behavior of ADI [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Austempering develops an ausferrite (ferrite and high carbon and stable austenite) microstructure. This unique microstructure (ausferrite) contributes standard mechanical properties to austempered gray cast iron (AGI) [4][5][6][7]. Therefore, AGI finds applications in the automobile industry as gears, pistons, cylinder liners, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Although, several research investigations on mechanical properties [4][5][6][7][8] and wear behavior [10][11][12][13][14] of austempered gray cast iron (AGI) have been carried out in the past, structured information on the effects of different austempering process parameters like alloy design, austenitizing temperature, austempering temperature and time of AGI is still lacking. Moreover, in the Indian context, cupola melting is the predominant mode of melting gray cast irons of wide section size ranges.…”
Section: Introductionmentioning
confidence: 99%